2001
DOI: 10.1209/epl/i2001-00522-9
|View full text |Cite|
|
Sign up to set email alerts
|

Multi-particle collision dynamics: Flow around a circular and a square cylinder

Abstract: A particle-based model for mesoscopic fluid dynamics is used to simulate steady and unsteady flows around a circular and a square cylinder in a two-dimensional channel for a range of Reynolds number between 10 and 130. Numerical results for the recirculation length, the drag coefficient, and the Strouhal number are reported and compared with previous experimental measurements and computational fluid dynamics data. The good agreement demonstrates the potential of this method for the investigation of complex flo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
263
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(271 citation statements)
references
References 16 publications
7
263
1
Order By: Relevance
“…However, because of this shifting, partially occupied cells can emerge when the simulation box and cell boundaries do not coincide with each other. This procedure is unavoidable for small mean free paths λ, and it has been demonstrated in ref 31 that the boundary conditions have to be appropriately modified in such a case. We have tested the validity of our implementation by applying a Poiseuille flow as described in ref 32 and found that the solvent velocity correctly extrapolates to zero at the system boundaries.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…However, because of this shifting, partially occupied cells can emerge when the simulation box and cell boundaries do not coincide with each other. This procedure is unavoidable for small mean free paths λ, and it has been demonstrated in ref 31 that the boundary conditions have to be appropriately modified in such a case. We have tested the validity of our implementation by applying a Poiseuille flow as described in ref 32 and found that the solvent velocity correctly extrapolates to zero at the system boundaries.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…In the thermostat, Eq. (3), we kept k B T = 0.01 (Lamura et al 2001). To verify our solutions, we used the least square fitting of Eq.…”
Section: Porous Channelmentioning
confidence: 99%
“…We will focus here on the multi-particle collision dynamics (MPC) technique [4,5,6], also called stochastic rotation dynamics [7] (SRD), originally developed for Newtonian fluids. This particle-based hydrodynamics method consists of alternating streaming and collision steps.…”
Section: Introductionmentioning
confidence: 99%